Seizure control for intracranial arteriovenous malformations is directly related to treatment modality: a meta-analysis. (6th December 2013) - Baranoski, Jacob F; Grant, Ryan A; Hirsch, Lawrence J; Visintainer, Paul; Gerrard, Jason L; Günel, Murat; Matouk, Charles C; Spencer, Dennis D; Bulsara, Ketan R
Abstract : Object: Seizures are a common presenting sign of intracranial arteriovenous malformations (AVMs). The object of this meta-analysis was to determine if the modality selected to treat AVMs affects the rate of seizure outcomes. Methods: All published data describing seizure status as an outcome goal over the past 20 years were included in this study. Seizure outcomes following microsurgery (MS), endovascular embolization for cure (EVE), or stereotactic radiosurgery (SRS) were compared using a validated random effect logistic regression approach. Results: 24 studies, with a total of 1157 patients, were analyzed. Overall, the microsurgical group had the best seizure control (p<0.01), with the relative predicted rates of seizure outcome as follows: MS 78.3% (95% CI 70.1% to 85.8%); SRS 62.8% (95% CI 55.0% to 70.0%); and EVE 49.3% (95% CI 32.1% to 66.6%). Patients in the SRS group who had complete obliteration of their AVMs achieved the highest rate of seizure control (85.2% (95% CI 79.1% to 91.2%); p<0.01). The development of new onset seizures occurred more frequently in patients undergoing EVE (39.4% (95% CI 8.1% to 67.8%)) compared with MS (9.1% (95% CI 5.0% to 13.1%)) and SRS (5.4% (95% CI 3.0% to 7.8%)) (p<0.3 and p<0.01, respectively). Conclusions: This is the first meta-analysis designed to study relative rates of seizure outcomes following the currently utilized AVM treatment modalities. In general, MS results in the highest proportion of seizure control. However, if SRS results in successful obliteration of the AVM, then this modality is the most effective in achieving seizure control.